Forced peeling and relaxation of neurite governed by rate-dependent adhesion and cellular viscoelasticity. (October 2020) - Gong, Ze; Fang, Chao; You, Ran; Shao, Xueying; Chang, Raymond Chuen-Chung; Lin, Yuan
Abstract: Tight connection between neural cells and their micro-environment is crucial for processes such as neurite outgrowth and nerve regeneration. However, characterizing neuron adhesion remains challenging because of its rate-dependent nature as well as its coupling with the viscoelastic cellular response. In this study, by conducting successive forced peeling and relaxation tests on the same neurite, we managed to extract both adhesion and viscoelastic characteristics of neural cells simultaneously for the first time. Specifically, well-developed neurites were peeled away from the substrate by an atomic force microscopy (AFM) probe under different loading rates and then held at a fixed separation distance for relaxation. A computational model was also developed to explain the observed peeling-relaxation response, where the neurite was treated as a standard linear viscoelastic material while a viscous-regularized cohesive law was introduced to represent neuron–substrate adhesion. Our combined experimental and simulation results indicated that the adhesion energy is of the order of 0.04–0.1 m J ∕ m 2, albeit being strongly rate-dependent, and relaxation takes place inside neurite with a characteristic time of ∼ 3 s. These findings could be critical for our physical understanding and modeling of different adhesion-mediated processes like neuron migration and synapse formation in the future.